PENGARUH ATRIBUT PRODUK ROTIBOY TERHADAP KEPUASAN KONSUMEN DI MALL CIPUTRA SEMARANG - Rosalia, Shelli; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2016)
One of the dominant factors for providing customer service is the satisfaction of consumers. Efforts must be made to satisfy customer needs profitably (win-win), the state in which both sides feel to win and no one harmed. Preservation of customer satisfaction with the company's sales volume is expected to be maintained, and even increased. Allegedly the factors that influence consumer satisfaction in this study, among others; affordability, product quality, product design and product reliability.The theory is used to generalize is as stated by Dutka (2010) which says that the product attributes of customer satisfaction are universally include 1) the value price relatons, 2) product quality, 3) product benefits, 4) product features, 5) product Deign, 6) product reliability and consistency, and 7) range of product or service. Dutka signal taken from the 4 factors of product attributes that are considered influential on consumer satisfaction Rotiboy, for reasons related data avaibilitas and visibility of the object, namely; affordability, product quality, product design and product reliability. Thus, the hypothesis is